Pelatihan Teknis Pengelolaan Pekerjaan Fisik Dana Desa untuk Peningkatan Kualitas Infrastruktur - Lita Istiyanti; Sri Kencanawaty; Hanifah Sabilla (FT Universitas Lampung, 2026)
Village Funds are a strategic government policy instrument aimed at accelerating rural development and improving community welfare. In practice, a substantial portion of Village Funds is allocated to physical infrastructure development, which requires adequate technical capacity and proper governance by village officials. Limited technical understanding in managing physical works often results in low infrastructure quality and increases the risk of administrative errors and potential legal problems. This community service activity aimed to improve the quality of village infrastructure by strengthening the technical capacity of village officials in managing Village Fund–based physical development projects through technical training.The activity was conducted using a community service approach consisting of technical training, interactive discussions, and case studies related to village physical works. The training materials focused on basic technical planning, volume calculation, quality control, and administrative reporting of physical development activities. Evaluation of the activity was carried out using pre-test and post-test assessments to measure changes in participants’ understanding. The results showed an improvement in participants’ technical comprehension, with average scores increasing from approximately 58% in the pre-test to 83% in the post-test. High participant engagement during discussion sessions indicated strong relevance between the training materials and practical challenges faced by village officials.These results demonstrate that technical training is effective in supporting better village infrastructure quality and serves as a preventive effort to reduce potential legal risks in Village Fund management.